Visual and efficient immunosensor technique for advancing biomedical applications of quantum dots on Salmonella detection and isolation. Issue 8 (8th February 2016) - Tang, Feng; Pang, Dai-Wen; Chen, Zhi; Shao, Jian-Bo; Xiong, Ling-Hong; Xiang, Yan-Ping; Xiong, Yan; Wu, Kai; Ai, Hong-Wu; Zhang, Hui; Zheng, Xiao-Li; Lv, Jing-Rui; et al.
Abstract : A visual immunosensor technique for efficient detection and isolation of Salmonella was established by applying fluorescent nanobioprobes on a cellulose-based swab. Abstract : It is a great challenge in nanotechnology for fluorescent nanobioprobes to be applied to visually detect and directly isolate pathogens in situ . A novel and visual immunosensor technique for efficient detection and isolation of Salmonella was established here by applying fluorescent nanobioprobes on a specially-designed cellulose-based swab (a solid-phase enrichment system). The selective and chromogenic medium used on this swab can achieve the ultrasensitive amplification of target bacteria and form chromogenic colonies in situ based on a simple biochemical reaction. More importantly, because this swab can serve as an attachment site for the targeted pathogens to immobilize and immunologically capture nanobioprobes, our mAb-conjugated QD bioprobes were successfully applied on the solid-phase enrichment system to capture the fluorescence of targeted colonies under a designed excitation light instrument based on blue light-emitting diodes combined with stereomicroscopy or laser scanning confocal microscopy. Compared with the traditional methods using 4–7 days to isolate Salmonella from the bacterial mixture, this method took only 2 days to do this, and the process of initial screening and preliminary diagnosis can be completed in only one and a half days. Furthermore, the limit of detection can reach as low as 10 1 cells per mL Salmonella on the background of 10 5 cells per mL non- Salmonella ( Escherichia coli, Proteus mirabilis or Citrobacter freundii, respectively) in experimental samples, and even in human anal ones. The visual and efficient immunosensor technique may be proved to be a favorable alternative for screening and isolating Salmonella in a large number of samples related to public health surveillance.